2010
DOI: 10.4081/ejh.2010.e46
|View full text |Cite
|
Sign up to set email alerts
|

Human dental pulp stem cells produce mineralized matrix in 2D and 3D cultures

Abstract: The aim of this study was to characterize the in vitro osteogenic differentiation of dental pulp stem cells (DPSCs) in 2D cultures and 3D biomaterials. DPSCs, separated from dental pulp by enzymatic digestion, and isolated by magnetic cell sorting were differentiated toward osteogenic lineage on 2D surface by using an osteogenic medium. During differentiation process, DPSCs express specific bone proteins like Runx-2, Osx, OPN and OCN with a sequential expression, analogous to those occurring during osteoblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…1,14,16,18-21 Odontoblasts are post-mitotic cells unable to proliferate, which makes their cultivation by traditional cell culture systems unsuccessful. Some authors have suggested culture methods for human odontoblasts based on the dissected crowns of molars, in which the pulp was removed and the odontoblast layer, attached to the walls of the pulp chamber, was cultured in cell medium 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,14,16,18-21 Odontoblasts are post-mitotic cells unable to proliferate, which makes their cultivation by traditional cell culture systems unsuccessful. Some authors have suggested culture methods for human odontoblasts based on the dissected crowns of molars, in which the pulp was removed and the odontoblast layer, attached to the walls of the pulp chamber, was cultured in cell medium 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β1 is one of the most abundant cytokines found in bone matrix and is a potent stimulator of tissue regeneration and a fibrogenic mediator, 15 and its ability to promote fibroblastic differentiation has already been investigated in other systems. 16,17 We chose TGF-beta1 treatment in order to significantly increase the differentiative potential of pulp cells and to accelerate the regeneration of functional dentin. Alizarin red staining, ultrastructural morphological analysis by electron microscopy, and biochemical assays of type 1 collagen, and DMP1 and DSP expressions were carried out to demonstrate the odontoblast phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…All procedures regarding collection of human samples were approved by the Provincial Ethics Committee of Santa Maria Nuova Hospital of Reggio Emilia. hDPSCs were isolated from dental pulp, as described in a previous study [8]. Briefly cells obtained from dental pulp were plated at clonal density (1.6 cells/cm 2 ) and after 6 days of culture, nodules originated by single cells were isolated from the culture plate, re-plated and expanded.…”
Section: Methodsmentioning
confidence: 99%
“…After 8 hours from cell seeding, 2 ml of the two osteogenic media were added to each sample. hDPSCs/collagen constructs were pre-differentiated for 10 days before in vivo implantation according to previous data [8], [10].…”
Section: Methodsmentioning
confidence: 99%
“…The confocal serial sections were processed with ImageJ software to obtain three-dimensional projections, as previously described [41]. The image rendering was performed by Adobe Photoshop software.…”
Section: Methodsmentioning
confidence: 99%